An Impact of Communicated Product Benefits on Consumer’s Evaluation of Gendered Products - Kniha, Darya; Gunina, Daria; Kincl, Tomáš, 1979-; Vysoká škola ekonomická v Praze. Fakulta managementu (2022)
This research is a partial replication of the original study that was conducted by Schnurr (2018). The main object of the current research was to examine how the communicated product benefits either functional or hedonic impact on consumer’s evaluation of gendered products within young adults (18-26 years old). The first part is literature research that provides an overview of existing studies. The theoretical part covers the topics such as aesthetic dimensions of packaging design elements, evaluation of gendered product, hedonic and func-tional goals of consumption and a conceptual congruity. Furthermore, this em-pirical work is based on existing research that suggests that gendered packag-ing design reinforces product evaluation (Tilburg et al., 2015). The study con-sists of two main parts, the first one is a pre-test, the second one is the main study. To investigate an interaction effect between product gender and prod-uct positioning several tests were conducted. It was revealed that there was a significant interaction between product gender and communicated product benefits on product evaluation.
Vedoucí práce: Daria Gunina
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses